Impact of using licorice root aqueous extract,.on Peking duck carcass - ahmed, alaa; sattar, haneen (University of Thi-Qar Journal of agricultural research, 2025)
The study conducted in one of the private fields for raising Peking ducks in Al-Muthanna Governorate, starting from 14/2/2025 to10/4/2025. 60 one-day-old Peking ducklings were raised from unsexed Peking ducks with an average weight of 42g. The ducklings were prepared from the local markets in Diwaniyah Governorate, to demonstrate the effect of studying different levels of aqueous extract of licorice on carcass of Peking ducks. The chicks were randomly assigned to four treatments, each with three replicates (5 chicks per replica). They were placed in twelve pens. The trial consisted of the following treatments: T1: Control treatment (no addition). T2: 5 ml of licorice aqueous/ L T3: 10 ml of licorice aqueous/ L T4: 15 ml of licorice aqueous/ L The results indicated the following: The addition of licorice aqueous extract to the drinking water of Peking ducks resulted in remarkable improvement. In the researched production traits, body weight, weight gain, and feed conversion ratio improvement were examined. The fourth treatment, which used 15 ml of licorice aqueous extract per liter of drinking water, produced the best results. The results showed a significant increase in the dressing percentage with and without edible viscera, the relative weight of edible viscera (giblet), and the relative weight of the main cuts, with a significant decrease in the secondary cuts of Peking duck carcasses treated with various levels of licorice aqueous extract, particularly at a concentration of 15 ml/liter of drinking water.